(untitled) (The Research of Medical Science Review, 2025)
Contrary to the stereotypical understanding of a grandiose narcissist, a vulnerable subtype of narcissism exists which is characterized by insecurity, hypersensitivity, and a tendency towards shame, anxiety, and depression. The purpose of the research was to develop an indigenous scale that helped assess both phenotypical presentations of narcissism, improving research on narcissism and reducing misdiagnosis. Using deductive method, the study was conducted in three phases. Item generation was followed by content validation assessment by three expert clinical psychologists. The Principal Component Analysis was conducted on a sample of university students (N=431) to explore the underlying structure of the scale, while the Confirmatory Factor Analysis was conducted on a separate sample (N=224) to confirm the factor structure and refine the scale items. PCA was conducted with Promax rotation which led to five component factor solution: Beliefs of Superiority, Social Manipulation, Protection of Vulnerable Self, Need for External Validation and Preoccupation with Success. The final solution explained total variance of 55% which was appropriate (Perez & Medrano, 2010). The reliability analysis of the scale and its subscales resulted in Cronbach’s alpha values greater than .70. The resulting structure was confirmed through CFA. The final model resulted in a 20-item scale which had adequate indices to show model fit (CMIN/df = 1.470, CFI = 0.92, GF1 = 0.90, RMSEA = 0.046 and PCLOSE = .681). The scale has two subscales for both presentations. The total score on the scale will help highlight individuals with traits of pathological narcissism.